Media Development Study Basic Techniques Of Handball Ball Based Adobe Flash Player On Coaching Extracurricular Son Handball Junior High School Level In Demak District - Sadullah, Akhmad; Kristiyanto, Agus; Purnama, Sapta Kunta (Program Studi Ilmu Keolahragaan - Universitas Pendidikan Indonesia, 2019)
AbstractThe background of this research is the unavailability of learning model of basic technique of hand ball which is used as a reference to build the ability of basic technique of hand ball among the students. The purpose of this research is to develop the basic technique of handball based technique of handball based on adobe flash player, including opening, passing, catch the ball, dribble, blocking, shoot the ball, goalkeeper training and stretching, all of which are arranged in one easily accessible media anytime, by anyone and anywhere, especially at the Se-degree Junior High School in Demak district. The research method used is